Current treatment of relapsed ovarian carcinoma - Bamias, A.; Rodolakis, A.; Dimopoulos, M.A. (Current Cancer Therapy Reviews, 2006)
Ovarian cancer is a leading cause of death from gynecological cancer. Although most patients will experience remission of their disease, following cytoreductive surgery and platinum (± paclitaxel) chemotherapy, relapse will occur in about 80% of cases with FIGO stages III and IV disease. Treatment of recurrent ovarian cancer represents a challenge. Cure is rare but long-term survival can be achieved in a significant proportion of patients. Treatment-free interval after first-line platinum-based chemotherapy determines sensitivity to platinum rechallenge. Nevertheless, other factors, such as symptoms, tumor bulk, ECOG PS and patients' preferences can also aid decision making in this setting. The recent ICON4/AGO and GCIC studies showed that combination of carboplatin with paclitaxel or gemcitabine are superior to carboplatin monotherapy in patients with platinum-sensitive disease, but at the expense of additional toxicity. Platinum refractory disease is associated with poor prognosis and monotherapy with a non-platinum agent, such as liposomal doxombicin, topotecan or a taxane is recommended. Biological agents targeting various components on cancer cells, such as vascular endothelial growth factor (VEGF), growth factors and stromal elements, are under investigation as adjuncts to chemotherapy. In addition, selected patients may benefit from surgery at recurrence, but they represent the minority of patients with relapsed ovarian cancer. © 2006 Bentham Science Publishers Ltd.
Keywords: Chemotherapy; Ovarian carcinoma; relapse; surgery